Oil Well Breakdown Pressure in Blasting Force Loading Condition - Wu, Fei-Peng; Chen, De-Chun; Pu, Chun-Sheng; Wei, Xue-Mei; Liu, Min (Asian Journal of Chemistry, 2014)
Based on the problem of the quantitative description of blasting well breakdown pressure, 19 experiments on rock cracking of 3 tensile strengths and 5 loading rates using the rock dynamic cracking simulation device were conducted. The experiments verify that the device can crack the small simulation hole immediately as well as offer loading rate below 153.17 MPa/ms, which can simulate the real blasting fracturing condition completely. Based on the regression analysis of experimental data, relationship between the difference value of dynamic/static breakdown pressure and the loading rate tends to be logarithm. The regression model presents a calculation error of 0.95 %. The results can help to ascertain minimum peak pressure in the design of detonation pressure as well as enhance the production of universal application and the success ratio.